Antropolingwistyka: przegląd problematyki - Zaniewski , Jan; Nizhneva, Natallia (Scripta Neophilologica Posnaniensia, 2020)
Anthropolinguistics is one the most recent theoretical and practical perspectives developed within the science of linguistics. As such, it focus on the central question of the evolution of human thinking and its reflection in language. It is proposed that on the basis of evolutionary processes, it is possible to put forth a view according to which any further development of humanity depends on the presence and steady development of specialist lexicon. It secures the advancement of humanity in science, industry and culture.